A STUDY OF HUMAN ERROR FACTORS ON MARITIME ACCIDENT RATES IN MARITIME INDUSTRY - Ismila Che Ishak; Mohamad Fitri Azlan; Shaiful Bakri Ismail; Norhayati Mohd Zainee (Asian Academy of Management Journal, 2019)
Human error is the result of human actions. It is an actual action in daily life that could cause an accident and an intentional infringement. The purpose of this research is to analyse three factors of human error, namely fatigue, communication, and lack of technical knowledge as the major contributors to the occurrence of accidents. In addition, it seeks to determine the relationship between these factors and accidents in the maritime industry. A number of 60 respondents from an oil and gas company, and a government agency located in Lumut, Perak, Malaysia participated in this research. The results show a strong positive relationship between the human factors which include fatigue, communication, and lack of knowledge towards the maritime accident rates. Among the three, the lack of technical knowledge is the highest contributing factor which could seriously cause accidents in the maritime industry.